Mechanical Modeling and Optimization for the New Improved Configuration of the FAST Feed Cabin - Yin, Jianing; Yao, Rui; Jiang, Peng (Journal of physics. Conference series, 2025)
The Five-hundred-meter Aperture Spherical radio Telescope (FAST) is the world’s largest and most sensitive single-dish spherical radio telescope, and with the rapidly increasing observational demand, the urgent plan to raise the observational zenith angle is proposed for FAST to expand the observational sky area. In this regard, based on the previously studied feed cabin configuration, this paper creatively proposes an improved configuration with fixed-length cables connected to sliders and in parallel with a telescopic rod. Given the essential difference between the improved configuration and the traditional cable-length-control configuration, this paper derives the geometric and mechanical models. And based on the actual observational need of FAST, an analytical mechanical optimization method is also proposed, which aims to minimize the variance between cable forces within bounded domains. Finally, there are some simulations to verify that the improved configuration can both meet the cable force safety requirement and the space limitation in the cabin, which means it can achieve at least 50° zenith angle observation for FAST. This research provides the theoretical method for this kind of special configuration and is also an important basis on the FAST upgrade.